2020
DOI: 10.1371/journal.pone.0243465
|View full text |Cite
|
Sign up to set email alerts
|

Survey about do-it-yourself closed loop systems in the treatment of diabetes in Germany

Abstract: Continuous glucose monitoring (CGM) improves treatment with lower blood glucose levels and less patient effort. In combination with continuous insulin application, glycemic control improves and hypoglycemic episodes should decrease. Direct feedback of CGM to continuous subcutaneous insulin application, using an algorithm is called a closed-loop (CL) artificial pancreas system. Commercial devices stop insulin application by predicting hypoglycemic blood glucose levels through direct interaction between the sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…Glycemic outcomes with a combination of DIY AID system types were reported in 6 studies, including 5 self-reported user outcome studies, and a retrospective observational cohort. Self-reported user outcomes involved a total of 1508 participants worldwide, with all studies reporting improvements in TIR and/or HbA1c with DIY AID use [ 5 , 33 , 36 , 40 , 47 ]. Jeyaventhan et al reported retrospective observational glycemic data with six months of DIY AID use in 30 individuals (50% Loop, 36.7% AndroidAPS, 13.3% OpenAPS), comparative to the same time period for 38 users of Commercial AID (Medtronic 670G).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycemic outcomes with a combination of DIY AID system types were reported in 6 studies, including 5 self-reported user outcome studies, and a retrospective observational cohort. Self-reported user outcomes involved a total of 1508 participants worldwide, with all studies reporting improvements in TIR and/or HbA1c with DIY AID use [ 5 , 33 , 36 , 40 , 47 ]. Jeyaventhan et al reported retrospective observational glycemic data with six months of DIY AID use in 30 individuals (50% Loop, 36.7% AndroidAPS, 13.3% OpenAPS), comparative to the same time period for 38 users of Commercial AID (Medtronic 670G).…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of episodes of hypoglycemia (n = 2), severe hypoglycemia (n = 2) and TBR (n = 7) were reported in a total of 9 studies [ 33 35 , 40 45 ], with improvements in these parameters reported with the use of all three DIY AID system types. TBR was reduced by 0.1–1.11% across the observational studies [ 41 , 42 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Da vielen Pumpenträgern die Verfügbarkeit von individualisierbaren, kommerziellen AID-Systemen nicht schnell genug vorangeht, hat sich zudem die sogenannte „Looper Community“ gebildet, deren Mitglieder frei im Internet verfügbare Open-Source-Lösungen verwenden, die aber hier nicht behandelt werden können. Die Zahl der Anwender von kommerziellen AID-Systemen und Open-Source-Lösungen für die künstliche Bauchspeicheldrüse nimmt zu 16 , 17 . Diabetesteams sollten daher darauf vorbereitet sein, diesen Anwendern in der täglichen Praxis zu begegnen 18 .…”
Section: Hintergrundunclassified
“…Da vielen Pumpenträgern die Verfügbarkeit von individualisierbaren, kommerziellen AID-Systemen nicht schnell ge-nug vorangeht, hat sich zudem die sogenannte "Looper Community" gebildet, deren Mitglieder frei im Internet verfügbare Open-Source-Lösungen verwenden, die aber hier nicht behandelt werden können. Die Zahl der Anwender von kommerziellen AID-Systemen und Open-Source-Lösungen für die künstliche Bauchspeicheldrüse nimmt zu [16,17]. Diabetesteams sollten daher darauf vorbereitet sein, diesen Anwendern in der täglichen Praxis zu begegnen [18].…”
Section: Prinzip Der Aidunclassified